Tingkat Kepuasan Siswa Terhadap Menu Makanan yang Disajikan dalam Penyelenggaraan Makanan di SMP Islam Terpadu Al- Fahmi Kota Palu 2019: The Level of Student Satisfaction With The Food Service At Al-Fahmi Integrated Islamic Middle School In Palu City 2019 - Nurjaya; Wery Aslinda; Kasmawati (Svasta Harena: Jurnal Ilmiah Gizi, 2020)
The provision of food service plays an important role in achieving optimal students health status in school. The purpose of this study is to determine the level of student satisfaction with food menus served in the organization of food at the Al-Fahmi Integrated Islamic Middle School in Palu City 2019. This research is a type of qualitative research with a descriptive approach. The sample in this study was the total of the population, namely all students in grades 7 and 8, amounting to 95 people in the Al Fahmi Integrated Islamic Middle School in Palu City. Data analysis used was univariate analysis. Data analysis began with transcripts and in-depth interviews. The results of this study indicate that of the 95 respondents, 91.6% expressed satisfaction with the taste of the food served. 89.5% expressed satisfaction with the appearance of the food served, 78.9% expressed satisfaction with the portion of food served, 94.7% expressed satisfaction with the level of maturity of the food served, 87.4% expressed satisfaction with the cleanliness of the food served. The conclusion of this study was that respondents were satisfied with the food served at the Al-Fahmi Integrated Islamic Middle School in Paluri City. Suggestions from this study should make students' dining rooms and divide portions of food so that all students get equally even portions of food.